2000
DOI: 10.1007/s10434-000-0758-6
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer With Cirrhosis of the Liver: Results of Esophagectomy in 18 Consecutive Patients

Abstract: Although cirrhosis has a high morbidity and mortality rate, Child-Turcotte A and B cirrhosis may not contraindicate curative esophagectomy for esophageal carcinoma. However, these patients need meticulous perioperative care to avoid postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 27 publications
1
31
2
Order By: Relevance
“…Not surprising is that the length of hospital stay (up to 68%) and total hospital charges (up to 45%) were also increased compared to noncirrhotic patients [8]. Indeed, all authors focusing on this topic reported on an increased mortality rate in cirrhotic patients, which varied from 4 to 54% [7,8,13,14,15,16,17,18,19,20,21]. Csikesz et al [8] found that (dependent on the type of surgery: cholecystectomy, colectomy, coronary artery bypass grafting, abdominal aortic aneurysm repair) cirrhotic patients had a 3.4- to 8-fold increased risk of death, whereas those with cirrhosis along with portal hypertension experienced a 7.8- to 22.7-fold increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprising is that the length of hospital stay (up to 68%) and total hospital charges (up to 45%) were also increased compared to noncirrhotic patients [8]. Indeed, all authors focusing on this topic reported on an increased mortality rate in cirrhotic patients, which varied from 4 to 54% [7,8,13,14,15,16,17,18,19,20,21]. Csikesz et al [8] found that (dependent on the type of surgery: cholecystectomy, colectomy, coronary artery bypass grafting, abdominal aortic aneurysm repair) cirrhotic patients had a 3.4- to 8-fold increased risk of death, whereas those with cirrhosis along with portal hypertension experienced a 7.8- to 22.7-fold increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known prognostic factors of survival are as follows: R0 resection, 40 26 The metastatic lymph node ratio 52 (the ratio of invaded-removed lymph nodes) is also an independent prognostic indicator in patients with distant lymph node metastases. 53 The presence or absence of laryngeal recurrent nerve node, 27 cervical node, [25][26][27]30,41 and celiac node metastasis 26 are also useful prognosticators.…”
Section: Five-year Overall Survival and Prognostic Factorsmentioning
confidence: 99%
“…Tachibana et al [32] reported postoperative morbidity and mortality rates after esophagectomy in patients with liver cirrhosis, 83.3 and 16.7%, respectively, while Lu et al [33]. reported rates of 31.3 and 25%, respectively; however, most of these patients were treated with TTE.…”
Section: Discussionmentioning
confidence: 95%
“…A few reports have addressed the frequency of complications and mortality after esophagectomy in esophageal cancer patients with liver cirrhosis [31][32][33]. Tachibana et al [32] reported postoperative morbidity and mortality rates after esophagectomy in patients with liver cirrhosis, 83.3 and 16.7%, respectively, while Lu et al [33].…”
Section: Discussionmentioning
confidence: 99%